Answer:
The equation has one solution at which y = -3.
Explanation:
To find the value of y, we need to isolate it from the rest of the equation.
- Add 2 to both sides of the equation.
- Divide by -3 on both sides of the equation.
- Simplify the equation if necessary.
![\displaystyle{-3y-2=7}\\\\-3y = 9\\\\\bold{y = -3}](https://img.qammunity.org/2021/formulas/mathematics/high-school/gx52bfja8x9idx3x47lpp9ixif3o5qha0v.png)
We can check to make sure that y = -3 by substitution.
![\displaystyle{-3(-3)-2 = 7}\\\\9-2=7\\\\7= 7 \ \checkmark](https://img.qammunity.org/2021/formulas/mathematics/high-school/kod8g9hjwltuw9kfstk7i12mvd6mmck1qb.png)
Because we got a true statement, we can determine that y = -3.